Activating mutations of the oncogene EZH2 in cutaneous melanoma revealed by next generation sequencing - Paul W. Harms; Alexandra C. Hristov; David S. Kim; Tobenna Anens; Michael J. Quist; Javed Siddiqui; Shannon Carskadon; Rohit Mehra; Douglas R. Fullen; Timothy M. Johnson; Arul M. Chinnaiyan; Nallasivam Palanisamy (Elsevier, 2014)
Enhancer of zeste homolog 2 (EZH2) is a histone methyltransferase that promotes tumorigenesis by epigenetic repression of tumor suppressor genes. Although EZH2 is overexpressed in many malignancies, activating EZH2 mutations have been described predominantly in follicular lymphoma and diffuse large B-cell lymphoma. EZH2 activating mutations in melanoma are not well described. Here, we report a case of cutaneous melanoma that displayed an EZH2 (Y641S) activating mutation detected by transcriptome sequencing as well as BRAF (V600K). The patient had concurrent follicular lymphoma that lacked both the EZH2 (Y641) and BRAF (V600K) mutations present in the patient's melanoma. Further, we screened publicly available sequence data and identified four additional melanoma cases harboring activating EZH2 mutation. Our findings provide additional evidence that activating recurrent EZH2 mutations occur in cutaneous melanoma, to our knowledge the first solid tumor shown to harbor such mutations. These tumors may be amenable to EZH2 inhibitor therapy.